History and prospects of flax genetic markers - Zhernova, Daiana A.; Pushkova, Elena N.; Rozhmina, Tatiana A.; Borkhert, Elena V.; Arkhipov, Alexander A.; Sigova, Elizaveta A.; Dvorianinova, Ekaterina M.; Dmitriev, Alexey A.; Melnikova, Nataliya V. (Frontiers in Plant Science, 2025)
Flax (Linum usitatissimum L.) is known as a dual-purpose crop, producing both fiber and oil, which have a wide range of uses. Successful flax breeding requires knowledge on the genetic determinants of flax traits. The former identification of molecular markers for valuable traits used labor-intensive and sometimes poorly reproducible approaches. However, they allowed an assessment of the genetic diversity of flax and its relatives, the construction of linkage maps, and the identification of some markers for important characteristics. The sequencing of flax whole genome triggered the development of genome-wide association studies (GWAS) and quantitative trait locus (QTL) mapping. QTLs and quantitative trait nucleotides (QTNs) were identified for valuable seed- and fiber-related features and for resistance to biotic and abiotic stressors. Cost-effective and accurate analysis of large number of genotypes for multiple markers simultaneously using microarrays or targeted deep sequencing became available, as well as HRM, TaqMan, KASP, and other fluorescence-based high-throughput methods for detecting DNA polymorphisms. However, most DNA markers identified in flax are ambiguously linked to trait expression and are not universally applicable. A major challenge remains the lack of knowledge on functional polymorphisms. To date, only a few are known, mainly mutations in the FAD3 genes responsible for reduced linolenic acid content in linseed oil. For the further development of marker-assisted and genomic selection of flax, it is necessary to analyze exhaustively phenotyped sample sets, to identify DNA polymorphisms that determine valuable traits, and to develop efficient DNA test systems.